Communication of Tax Counseling to New Taxpayers Categorized as Entrepreneurs at Tapaktuan Tax Office - Nurgraha Martuah Purba; Humaizi Humaizi; Nurbani Nurbani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The objective of the research was to analyze the communication process of tax counseling, analyze the perception of New Taxpayers Categorized as Entrepreneurs about tax counseling communication, and analyze the obstacles in the communication process of tax counseling to New Taxpayers Categorized as Entrepreneurs in Tapaktuan Tax Office. Constructivism and qualitative method were use for the paradigm. The data were gathered by conducting observation and in-depth interviews. Informants were determined using purposivetechnique so that there were 12 informants consisting of 9 main informants and 3 triangulation informants.  The results of the research showed that the counseling communication process begins when the New Taxpayer Categorized as Entrepreneurs registers NPWP. Eight key informants in this study said they were quite familiar with the tax counseling materials provided by tax officials and 1 main informant admitted that he did not understand the tax counseling he received. The barriers to counseling communication that the main informants experience are physical barriers, technical barriers and human barriers. Physical obstacles were experienced by informants because the condition of the Tapaktuan Tax Office which was very crowded during the counseling slightly disturbed their concentration in receiving counseling materials. One informant experienced technical and human barriers. The physical condition of the informant did not allow him to be able to understand the tax counseling material. The Informant also ignored the tax counseling materials given to him because he reasoned that registering a NPWP was only to make a loan at the bank.